Disseminated intravascular coagulation syndrome as a complication in acute spontaneous canine babesiosis - Oksana A. Dubova; Diana V. Feshchenko; Tetiana I. Bakhur; Oksana A. Zghozinska; Anatoliy A. Antipov; Serhii V. Rublenko; Volodymyr P. Goncharenko; Raisa V. Shahanenko; Volodymyr S. Shahanenko (Macedonian Veterinary Review, 2020)
The polyetiological syndrome of disseminated intravascular coagulation (DIC) is characterized by changes in patients’ hemostasis. The aim of the current research was to elucidate the main factors for the development of DIC syndrome during canine babesiosis, and to assess their correlation level. Dogs included in this study were of various breeds and sex, weighing 10-40 kg and aged 2-7 years. They were separated in two groups (n=50) according to their diagnosis to babesiosis. Oscillometry (blood pressure, pulse rate), vascular-platelet hemostasis, coagulogram, hematological, biochemical (fibrinogen, fibrin degradation product, soluble fibrin-monomer complex) and hemodynamic (circulating blood volume) assessment methods were used. The group of dogs positive on Babesia spp., had clear manifestation of DIC with 5-7% of the erythrocyte population being affected. DIC was manifested by a significant increase in soluble fibrin-monomer complex and fibrin degradation product (p<0.001), hypofibrinogenemia (p<0.001), thrombocytopenia (p<0.001), and an increase in indicators of spontaneous aggregation ability of platelets and red blood cells (p<0.001). Significant hemodynamic disorders were observed: a decrease in circulating blood volume, circulating erythrocytes volume (p<0.05), specific circulating blood volume and hematocrit value (p<0.001). The average blood pressure was reduced (p<0.001), and the Allgöwer’s shock index was increased 2 times (p<0.05). A shock of II degree (medium, subcompensated) was confirmed. Therefore, it can be concluded that acute spontaneous dogs’ babesiosis can be characterized by the occurrence of DIC in a consumption coagulopathy form, and shock of II degree. This condition renders the patients for emergency admission.